2011
DOI: 10.1589/jpts.23.741
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plantar Hardness Discrimination Training on Center-of-Gravity Sway while Standing on One Leg: a Randomized Controlled Trial

Abstract: Abstract. [Purpose] We investigated the influence of plantar hardness discrimination training on center-of-gravity sway while standing on one-leg.[Subjects] Twenty healthy adult volunteers were randomly divided into intervention (n = 10) and control groups (n = 10).[Methods] The intervention group subjects carried out 10-day plantar hardness discrimination studies on sponges with 5 different levels of hardness. The control group underwent the same training except that they were not instructed to discriminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…None of these had participated in earlier studies by our group. [13][14][15][16][17] Individuals were selected according to the following inclusion criteria: age 65 years or older, community dwelling, had not visited a primary care physician within the previous 12 months, ability to walk independently, and a Mini-Mental State Examination 23 score of 24 or greater. We also used an interview to exclude participants based on the following exclusion criteria: severe cardiac, pulmonary, or musculoskeletal disorder; pathologies associated with increased risk of falls, such as Parkinson's disease or stroke; osteoporosis; the use of psychotropic drugs; and peripheral neuropathy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of these had participated in earlier studies by our group. [13][14][15][16][17] Individuals were selected according to the following inclusion criteria: age 65 years or older, community dwelling, had not visited a primary care physician within the previous 12 months, ability to walk independently, and a Mini-Mental State Examination 23 score of 24 or greater. We also used an interview to exclude participants based on the following exclusion criteria: severe cardiac, pulmonary, or musculoskeletal disorder; pathologies associated with increased risk of falls, such as Parkinson's disease or stroke; osteoporosis; the use of psychotropic drugs; and peripheral neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…Procedures described below were in accordance with those in previous studies. [13][14][15][16][17] We used squares of sponge mat (INOAC, Aichi, Japan) with five different levels of hardness (58.8, 78.5, 107.9, 200, 308 N/100 πcm 2 ), as measured by an automatic hardness tester (type JIS K6400, Asker JA). All were made of the same material and were of the same size (30 cm × 30 cm 2 × 40 mm thick).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects performed a plantar perceptual learning task with sponges of different hardness that were arranged on the floor [1][2][3][4][5] . We used squares of sponge mat with the five different levels of hardness (INOAC Co., Aichi, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Morioka et al reported that the center-ofgravity sway and FRT of hemiplegic stroke patients, as well as elderly and very old individuals, were improved significantly by the task [2][3][4] . Moreover, we reported that the center-of-gravity sway of healthy adults, while standing on one leg, was improved significantly by the task 5) . These reports demonstrate that postural control improves through plantar perceptual learning.…”
Section: Introductionmentioning
confidence: 91%